Does broad money matter for interest rate policy? - Matthias Brückner; Andreas Schabert (Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), 2002)
This paper presents a business cycle model with financial intermediation encompassing the conventional New Keynesian model. Households' financial wealth comprises cash and interest bearing deposits. When deposits provide transaction services, real broad money, which is predetermined, affects aggregate demand and has a stabilizing impact. Monetary policy can ensure equilibrium uniqueness if the central bank reacts at least slightly on the real broad money gap. Moreover, if the central bank aims at minimizing a standard loss function, real broad money enters the interest rate reaction function. Thus, money matters if it is defined broadly enough to include all households' financial assets.
Keywords: E52; E51; E41; E32; 330; Interest rate policy; real broad money; financial wealth; macroeconomic stability; Zinspolitik; Konjunkturpolitik; Geldmenge; Ungleichgewichtstheorie; Konjunkturtheorie; Vermögenseffekt